Firm Productivity and Matching Frictions in th Labor Markets: Is This an Unending Curse to Employers? - Ndolo, David Katuta; Senelwa, Victor Kidake (European Scientific Journal, ESJ, 2023)
The productivity behavior of firms is significantly influenced by labor market frictions in both emerging and established economies. Kenya persistently advocates for enhanced strategies to bolster productivity. The precise impact of labor market friction remains ambiguous. This paper focuses on assessing the influence of qualification and skills mismatch on firm productivity within the context of Kenya. The study utilized secondary crosssectional data obtained from the World Bank database, specifically from the 2016-2017 Skills Toward Employment Productivity (STEP) Household Survey conducted in Kenya. The full specification of the maximum likelihood model under the endogenous switching regression (ESR) was estimated. The results of the study indicate that insufficient education and a mismatch between skills and job requirements have a significantly negative impact on firm productivity. The impact of excessive education on firm production was found to be minimal. The essential finding regarding the marginal treatment effect, which holds significant implications for policymaking, indicates a strong positive association between over-education and firm productivity. A negative association is observed between education and skills mismatch and firm productivity. The policy implications underscore the necessity of aligning graduates with employment opportunities that correspond to their educational background and level of expertise.